Настрої та поведінка населення Києва у часи аварії на Чорнобильській АЕС (до 30-річчя Чорнобильської трагедії) - Бажан, О. (Краєзнавство, 2016)
У статті описано інформаційну ситуацію навколо вибуху на 4-му енергоблоці Чорнобильській АЕС, розкрито комплекс заходів радянських спецслужб по засекреченню відомостей про аварію на режимному об'єкті, висвітлюється морально-психологічний стан жителів Києва у пост-чорнобильський період. В статье описано информационную ситуацию вокруг взрыва на 4-м энергоблоке Чорнобыльской АЭС, раскрыто комплекс мероприятий советских спецслужб по засекречиванию фактов об аварии на режимном объекте, освещается морально-психологическое состояние жителей Киева у пост-чернобыльский период. Information about the man-made disaster caused by the explosion and subsequent destruction of the fourth unit of the Chernobyl nuclear power plant on the night of April 26, 1986, was immediately classified as secret bythe Party and State leadership of the Soviet Union and Soviet secret services. State Security Committee of the Council of Ministers of the USSR developed and implemented a range of special measures for makingsecret the information on the accident in the regime zone. Not giving up the May Day demonstration in the capital of Ukraine, the political leadership of the Ukrainian SSR intended to use the international sport competition (the 39thinternational cycling race for peace) and business activities (the exhibition "Beet-86")as a tool to neutralize the negative impressions of the Chernobyl event. Hoping to downplay the scale of the tragedy, the State Security members considered it necessary not to disclose to the press and privately the causes of the accident on the Chernobyl4thunit; statistics incidence of radiation sickness among the plant personnel, liquidators, evacuees; the name of organizations and number of employees who were involved in the liquidation work. The hiding of the catastropheextent by the government agencies, the speculations of foreign radio stations gave rise to incredible rumors and disturbing fear among Kyiv residents. The dosed and sometimes distorted information about the existing danger, ignorance of how to behave in an emergency situation created conditions for mass and long-time panic in the capital of Ukraine. Chernobyl disaster caused the fracture of normal life, everyday behavior. Soviet government wickedness in concealing the extent of the accident led to increased distrust in the authorities and disbelief in their ability to effectively overcome the negative effects of radioactive pollution. The accident at 4th unit of the Chernobyl nuclear power plant has had a radical impact on Ukrainian society and has provoked significant social and political transformation processes in Ukraine.